Quantifying the physical demands in non-elite field hockey to develop training guidelines that minimise injury through adequate preparation - McManus, Alexandra; Stevenson, M. (Sports Medicine Australia, 2007)
Players need a high level of energy and analytical skill to fulfil the requirements of a field hockey game. Sports-specific physical training is paramount in field hockey. Few published studies have focused on the demands placed on participants at non-elite level. This study quantified the positional demands of both male and female non-elite competitors with the view to developing guidelines to test players preparedness to compete. This study found that there were few significant differences between the demands placed on players by position or gender with players performing between 510 and 520 separate movements per game, changing movements every 8-11 seconds. Differences existed between the number and utility movements in both genders however male defenders completed significantly more high intensity movements in comparison to female attack players. On average players in both genders completed up to 300 moderately high or high intensity movements over a game with more intense anaerobic efforts required towards the end of playing periods. The findings of this study indicate the need for gender-specific basic skills and fitness programs with two additional components addressing the differing needs of midfielders and defences (similar) and the attacks. This paper will present evidence for the development of performance tests that cater for the significant differences between the demands of each position. The tests can be used to assess player preparedness to compete, if ready to return to play following injury or if fatigued during the season.